Hubungan Aspek Kualitas Pelayanan Dengan Kepuasan Pasien Rawat Inap - maryana maryana; Maya Christiany (STIKES Citra Delima Bangka Belitung, 2022)
Patient satisfaction is one indicator of success obtained from the patients. The standard of outpatient satisfaction according to the Ministry of Health in 2016 is above 90%. Patient satisfaction is one indicator of the quality of services we provide and patient satisfaction is a capital to get more patients and to get loyal patients. The purpose of this study was to determine the aspect of service quality on the satisfaction of inpatients at the DepatiBahrin Hospital Sungailiat Bangka. For the work area at the Depati Bahrin Sungai liat General Hospital, inpatient satisfaction has increased in the last 3 years. In 2018 it was 81.50%, in 2019 it was 83%, in 2020 it was 84.56%. This study was conducted using a cross sectional design and chi-square test with the results in the form of bivariate analysis and univariate analysis. The research population is hospitalized patients in June 2021. The research sample is mostly aged > 18 years from the study population, which amounted to 83 respondents. The research instrument used a questionnaire containing 21 questions. The results showed that there was a relationship between reliability p value (0.000), responsiveness p-value (0.000), physical evidence p-value (0.029), assurance p-value (0.000), empathy p-value (0.038) and patient satisfaction in inpatient services. Suggestions from this study are to improve the performance and quality of the factors of reliability, responsiveness, physical evidence, assurance, and empathy so that inpatient satisfaction indicators increase.